Antitussive, anti-pyretic and toxicological evaluation of Ma-Xing-Gan-Shi-Tang in rodents. Issue 1 (December 2016) - Lin, Yu-Chin; Chang, Ching-Wen; Wu, Chi-Rei
Abstract Background Ma-Xing-Gan-Shi-Tang (abbreviated as MXGST), an important Chinese herbal prescribed for cough, bronchial inflammation and fever from pneumonia, consists of four medicinal herbs, including Ephedrae herb, Semen Pruni Armeniacae, licorice and Gypsum. These components, especially Ephedrae and Semen Pruni Armeniacae, possess antitussive activities, but they have severe adverse effects. Methods The pharmacological activities of MXGST extract in clinical use were investigated with citric acid-induced cough, acetylcholine/histamine-induced bronchial contraction and lipopolysaccharide (LPS)-induced fever in rodents. The subacute toxicology of MXGST extract was evaluated after a 28-day repeated oral administration in rats. Results Each gram of MXGST extract contained 60 ± 8 μg of ephedrine, 480 ± 40 μg of glycyrrhizic acid and 440 ± 8 μg of amygdalin according to high performance liquid chromatography and a photodiode array detector. MXGST extract produced pronounced, dose-dependent antitussive effects in guinea pigs and reduced hyperthermic syndrome induced by LPS in rats. MXGST extract blocked the bronchial contraction induced by acetylcholine/histamine. Oral administration of MXGST extract for 28 days did not cause any hematological, biochemical or histological changes in rats. Conclusions MXGST extract is a safer, more effective Chinese prescription with antitussive and anti-pyretic effects. The antitussive mechanism of MXGST is related to partially relaxing the bronchial smooth muscle by blocking acetylcholinergic and histaminergic receptors.